Dampak Penyakit Kronis Terhadap Peluang Terjadinya Kerentanan Pada Rumah Tangga Di Indonesia - Dita Desriani; Prani Sastiono (ITB AAS Indonesia Surakarta, 2023)
Welfare and health analysis in developed countries is the primary focus of various policies. The poor population health due to chronic diseases emerges as a vulnerability and threat to the country's economic stability. One of the chronic diseases that causes the highest global morbidity and mortality is hypertension. The burden or costs incurred due to hypertension are not only suffered by the patients but also for other household members, including paying for medical expenses. Thus, this study aims to estimate vulnerability due to hypertension using the vulnerability of expected poverty (VEP) method. This study employed data from the fourth and fifth waves of IFLS. The VEP calculation was done using the three-step feasible generalized least squares (FGLS) method. The results showed that households with hypertension tended to have lower consumption expectations than households without hypertension. Therefore, hypertension significantly increases household vulnerability in the future. Keywords : Health condition, poor household, vulnerability of expected poverty, three-step feasible generalized least squares (FGLS)